Psychometric Properties of Object Relation Scale: Factor Structure and Relationship to Mental Health - Uji, Masayo; Kawaguchi, Makiko (Advances in Social Sciences Research Journal, 2021)
Background: Object Relations Scale (ORS: Iume, Hirai, Aoki & Baba, 2006) was developed for accessing an individual’s object relation pattern. It consists of five domains: Insufficiency of Intimacy, Superficiality in Interpersonal Relations, Egoistic Manipulation, Excessive Need for Identification, and Abandonment Anxiety. However, its factor structure using confirmatory factor analysis (CFA) is still undetermined. Purpose: This study aims at evaluating the psychometric properties of ORS, in particular, confirming its factor structure using CFA, and examining the relationship of object relation maturity, to mental health as well as to psychological distress. Methods: The subjects of this study were 547 medical college students in Japan. CFA were conducted in order to determine the best fit model. The relationships of maturity level of one’s object relation pattern to his/her mental health as well as psychological distresses were examined by t-tests. Results: A four-factor model, a modified version of the original five-factor model showed the best fit. Among the four factors, three were those included in the original model. They were Insufficiency of Intimacy, Superficiality in Interpersonal Relations, and Abandonment Anxiety. The last factor consisted of items originally included in the remaining two factors, Egotistic Manipulation and Excessive Need for Identification. Each ORS subscale score positively correlated with that of mental health problems as well as those of psychological distresses of one or more domains at significant levels. Conclusion: The four-factor model, which does not necessarily negate the original five-factor model proposed by Iume et al., showed the best fit. Immaturity and instability in object relation relationship contributed to a variety of distresses as well as poor mental health.